Perception of Students of Polytechnic Sultan Idris Shah, Selangor, Towards the Application of Learning Module - Abas, Mohd Khir Johari; Kassim, Nahrawi; Ibrahim, Asma (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
The modular learning method is essential for helping students reinforce their understanding and to enhance excellence. To demonstrate the actual impact of the module on the students’ learning, it is necessary to evaluate the students’ impressions and perceptions of the created module. This study aims to determine how students in the second semester of the Introduc-tion to Islamic Law (KPPI) course at Polytechnic Sultan Idris Shah perceive the application of learning module. The constructs tested in this study are learning module evaluation, learning module function and students’ ac-ceptance. The study design is descriptive by applying a quantitative approach through the questionnaire (sur-vey instruments). From a pilot study of 30 students, the Cronbach’s alpha reliability value received was 0.973. This study applied SPSS 26.0 software to analyze data in the form of frequency, mean, percentage, and standard deviation. Respondents consisted of 70 second semes-ter students who took KPPI. Collectively, the research findings demonstrated that the mean and standard devi-ation of the module evaluation construct, module func-tion and students’ acceptance were high. This proves that the KPPI learning module assists students in en-hancing their comprehension, generating interest, and displaying positive acceptance. The research findings also prove that the application of learning module is still the main choice as a learning aid in creating a learning environment conducive to excellence.